Deepening of the New Digital-Based Marketing Concept and Its Impact on Purchasing Decisions and Word of Mouth - Suniya Suniya; Pristiyono Pristiyono; Marlina Siregar (Journal of Global Business and Management Review, 2023)
The purpose of this study is to empirically prove the role of viral marketing, turbo marketing, and brand ambassadors to influence purchasing decisions and their impact on word of mouth. The concept of this research carries a descriptive research approach. The population is the people of Labuhanbatu Regency, total 499,982. The researcher applied the Slovin formula to obtain a minimum sample, which sample is 99.98 or fulfilled into 100 respondents. The sampling technique chose simple random sampling. All indicators that form the variables studied are processed through validity and reliability tests. Data analysis uses the SmartPLS 4.0 application. The result is viral marketing influences purchasing decisions online otherwise there is no relationship with word of mouth. Turbo marketing does not support purchasing decisions and word of mouth. Brand ambassadors affect online purchasing decisions, while purchasing decision is not significant to word of mouth